(untitled) (Research, Society and Development, 2020)
Objective: to discuss some psychosocial, psychological, emotional and interpersonal aspects caused by COVID 19. Method: theoretical study in government documents thath ighlight recommendations for preventing and coping with this pandemic, in the physical and mental health areas. Results: the pandemic is an event considered unique in the history of societies around the world. Stress, anxiety, panic, fear, fear, insomnia, disability, idleness, among others, are emotions that canoccur with the imagined and real proximity of being affected by COVID-19, and also potentiated by the excessive stimulation of the media and by countless fake News, thus leaving people with emotions in full swing. Conclusion: It is up to each one to recover emotionally in the singular daily life; and social groups to institute equitable practices in the economic dimension. In this sense, this study highlights the importance of offering interdisciplinary and holistic treatments in public health systems, since the approach to the body, only in specialties, does not favor diagnosing and preventing psychological and mental suffering.